(3haGI SjOfG EHQGgje Ydjg GdSdGes - (3eLghds ((3eMeO GdegOGhjs)
(3ChdgG (B:s
(3Qhi Cfg cGf ddfHj Udi Gddg Ydjg hSde CQHYI ChdGO GdWjH hGdbGSe hEHQGgje hcGf EHQGgje MSfg cMSf jhSa Ydjg GdSdGe aj hLgg hUhJg cUhJ OGhhOs
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde de dHSJ gPG GdShGO bGd dHSJg edGFcI GdSehGJ cdgG ef TCf GHfc EHQGgje UdhGJ Gddg Ydjgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs